Plantation Mapping in Southeast Asia - Jia, Xiaowei; Khandelwal, Ankush; Carlson, Kimberly; Gerber, James S.; West, Paul C.; Kumar, Vipin (Frontiers in Big Data, 2019)
Plantation mapping is important for understanding deforestation and climate change. While most existing plantation products are created manually, in this paper we study an ensemble learning based framework for automatically mapping plantations in southern Kalimantan on a yearly scale using remote sensing data. We study the effectiveness of several components in this framework, including class aggregation, data sampling, learning model selection and post-processing, by comparing with multiple baselines. In addition, we analyze the quality of our plantation mapping product by visual examination of high resolution images. We also compare our method to existing manually labeled plantation datasets and show that our method can achieve a better balance of precision (i.e., user’s accuracy) and recall (i.e., producer’s accuracy).